A bio-conjugated chitosan wrapped CNT based 3D nanoporous architecture for separation and inactivation of Rotavirus and Shigella waterborne pathogens. Issue 48 (30th November 2017) - Pramanik, Avijit; Jones, Stacy; Gao, Ye; Sweet, Carrie; Begum, Salma; Shukla, Manoj K.; Buchanan, Janice Paige; Moser, Robert D.; Ray, Paresh Chandra
Abstract : The multifunctional bio-conjugated 3D architecture reported here represents huge advances in the fields of environmental remediation and sustainable remediation. Abstract : The United Nations (UN) estimates that more than one billion people in this world do not have access to safe drinking water due to microbial hazards and it kills more than 7.6 million children every year via waterborne diseases. Driven by the need for the removal and inactivation of waterborne pathogens in drinking water, we report the chemical design and details of microscopic characterization of a bio-conjugated chitosan attached carbon nanotube based three dimensional (3D) nanoporous architecture, which has the capability for effective separation and complete disinfection of waterborne pathogens from environmental water samples. In the reported design, chitosan, a biodegradable antimicrobial polysaccharide with an architecture-forming ability has been used for the formation of 3D pores as channels for water passage, as well as to increase the permeability on the inner and outer architectures for killing Rotavirus and Shigella waterborne pathogens. On the other hand, due to their large surface area, CNTs have been wrapped by chitosan to enhance the adsorption capability of the architecture for the separation and removal of pathogens from water. The reported data show that the anti- Rotavirus VP7 antibody and LL-37 antimicrobial peptide conjugated chitosan–CNT architecture can be used for efficient separation, identification and 100% eradication of Rotavirus and Shigella waterborne pathogens from water samples of different sources. A detailed mechanism for the separation and inactivation of waterborne pathogens using the bio-conjugated chitosan based 3D architecture has been discussed using microscopic and spectroscopic studies. Reported experimental data demonstrate that the multifunctional bio-conjugated 3D architecture has good potential for use in waterborne pathogen separation and inactivation technology.